A genetic trend in a herd of pigs of farmbreeding type «Bagachansky» of the Large White breed - Березовський, М. Д.; Ващенко, П. А.; Хатько, І. В. (Scientific Progress & Innovations, 2012)
During 2002–2010 the estimation of breeding (genetic) value of pigs of farmbreeding type «Bagachansky» of the Large White breed was conducted by BLUP method. On the basis of obtained data the genetic trend in a population for basic productive traits was characterized. It was established that the phenotypic estimation of high heritability traits vary proportionately with genetic trend. There are also some differences, for example, the animals of a foreign selection which were used in 2004 could not show up their genetic potential because of housing conditions and feeding.